Pelatihan Pengelolaan SDM Era Digital Pada UMKM Kota Batam - Sabri Sabri; Rahman Syahputra; M. Fadli Luran; Amirullah Amirullah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
One of the challenges faced by MSMEs in the era of digital economic transformation is the lack of human resource (HR) skills in adapting trading methods from conventional business models to online business models. The progress and complexity of digital transformation that continues to increase daily offer many benefits for today's business world. This service aims to add knowledge to MSMEs assisted by the Batam City Cooperative and Small Business Office in overcoming challenges that arise due to changes in the digital era, especially in terms of Human Resources (HR) management. The method in this service is lectures, discussions, and questions and answers as well as evaluation. This activity includes delivering information and understanding effective strategies and techniques for managing human resources in the digital era